Aseptic lymphocyte-dominated vasculitis-associated lesions are related to changes in metal ion handling in the joint capsules of metal-on-metal hip arthroplasties. Issue 6 (June 2018) - Langton, D. J.; Sidaginamale, R. P.; Joyce, T. J.; Bowsher, J. G.; Holland, J. P.; Deehan, D.; Nargol, A. V. F.; Natu, S.
Abstract : Objectives: We have encountered patients who developed large joint fluid collections with massive elevations in chromium (Cr) and cobalt (Co) concentrations following metal-on-metal (MoM) hip arthroplasties. In some cases, retrieval analysis determined that these ion concentrations could not be explained simply by the wear rates of the components. We hypothesized that these effects may be associated with aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL). Patients and Methods: We examined the influence of the ALVAL grade on synovial fluid Co and Cr concentrations following adjustment for patient and device variables, including volumetric wear rates. Initially restricting the analysis to include only patients with one MoM hip resurfacing device, we performed multiple regression analyses of prospectively collected data. We then repeated the same statistical approach using results from a larger cohort with different MoM designs, including total hip arthroplasties. Results: In the resurfacing cohort (n = 76), the statistical modelling indicated that the presence of severe ALVAL and a large fluid collection were associated with greater joint fluid Co concentrations after adjustment for volumetric wear rates (p = 0.005). These findings were replicated in the mixed implant group (n = 178), where the presence of severe ALVAL and a large fluid collection were significantly associated with greater fluid Co concentrations (p < 0.001). Conclusion: The development of severe ALVAL is associated with elevations in metal ion concentrations far beyond those expected from the volumetric loss from the prosthetic surfaces. This finding may aid the understanding of the sequence of events leading to soft-tissue reactions following MoM hip arthroplasties. Cite this article : D. J. Langton, R. P. Sidaginamale, T. J. Joyce, J. G. Bowsher, J. P. Holland, D. Deehan, A. V. F. Nargol, S. Natu. Aseptic lymphocyte-dominated vasculitis-associated lesions are related to changes in metal ion handling in the joint capsules of metal-on-metal hip arthroplasties. Bone Joint Res 2018;7:388–396. DOI: 10.1302/2046-3758.76.BJR-2018-0037.